Surface tensions of binary mixtures of ionic liquids with bis(trifluoromethylsulfonyl) imide as the common anion - Oliveira, M. B.
While values for thermophysical properties of ionic liquids are becoming widely available, data for ionic liquid mixtures are still scarce. In an effort to overcome this limitation and understand the behavior of ionic liquid mixtures, novel data for the surface tension of mixtures composed of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [C(4)mim][NTf2], with other ionic liquids with a common anion, namely 1-butyl-2,3-dimethylimidazolium, [C(4)C(1)mim](+), 3-methyl-1-propylpyridinium, [C(3)mpy](+), 1-methyl-1-propylpyrrolidinium, [C(3)mpyr](+), and 1-methyl-1-propylpiperidinium, [C(3)mpip](+), were measured at T = 298.2 K and atmospheric pressure over the entire composition range. From the surface tension deviations derived from the experimental results, it was possible to infer that the cation alkyl chain length of the second ionic liquid constituting the mixture has a stronger influence in the ideal mixture behavior than the type of family the ionic liquid cation belongs to. The Gibbs adsorption isotherms, estimated from the experimental values, show that the composition of the vapor-liquid interface is not the same as that of the bulk and that the interface is richer in the ionic liquid with the lowest surface tension, [C(4)mim][NTf2]. (C) 2013 Elsevier Ltd. All rights reserved.